ELECTROMAGNETIC COMPATIBILITY OF WIRELESS NETWORKS IEEE 802.11AC - ЛАЗЕБНИЙ, В. С.; ОМЕЛЬЯНЕЦЬ, О. О. (Technologies and Engineering, 2024)
Purpose. The purpose of these studies is to analyze the service area parameters of the access point of IEEE 802.11ac network, depending on the modulation and coding parameters, as well as the mutual influence of adjacent networks of this specification on the stability of their operation. Methodology. Based on the standardized parameters of the access point radiation power and the minimum required level of the received signal, the calculation of the maximum distance from the access point to the subscriber station of IEEE 802.11ac standard local network, at which it is possible to receive of data frames, under a certain mode of modulation and coding (MCS), was made. The obtained results were used to evaluate the level of electromagnetic compatibility of adjacent wireless networks of the IEEE 802.11ac specification. Findings. It has been established that under the conditions of limiting the radiated power of the access point at the level of 100 mW, high-speed data transmission modes in the IEEE 802.11ac wireless network can be realized within a radius of 10÷15 m from the access point when the interference in the path of radio wave propagation are absent. The size of the service area depends on the modulation and coding mode used in the network, and the radius of the area can vary up to ten times. The size also depends on the width of the frequency band of the radio channel and decreases by half, by increasing of the frequency band by four times. When the radiated power of the access point is reduced to 60 mW, the radius of the service area is reduced by 25%. Based on the results of the analysis of frequency channel occupancy assessment mechanisms used in IEEE 802.11 networks, it was concluded that in locations with a dense location of local networks, there can be a significant mutual influence, both due to influence of co-channel interference and due to inter-network interferences of adjacent frequency channels. Originality. Factors affecting the operation of adjacent wireless networks of the IEEE 802.11 standard at the physical level are summarized and numerical data characterizing the dependence of parameters of the service area of the IEEE 802.11ac access point by the data transmission mode is determined. Practical value. The results can be used during the design, planning and maintenance of IEEE 802.11 wireless standard networks to form a predictive estimate of the data transfer rate depending on the location of the user station in the service area of the access point and the presence of obstacles on the path of the OFDM signal propagation and by taking into account of others located nearby networks IEEE 802.11.